Facets of Shi'ite Islam in contemporary Southeast Asia (II) : Malaysia and Singapore - Marcinkowski, Christoph (2009)
The present paper is the sequel to the author's IDSS Working Paper "Facets of Shi'ite Islam in Contemporary Southeast Asia (I): Thailand and Indonesia". In an earlier IDSS Working Paper, the author has also tried to address some issues pertaining to Twelver Shi'ite Islamic thought, as well as conceptual and practical aspects.